Adolescent drinking onset and its adult consequences among men: a population based study from India. Issue 10 (5th August 2014) - Pillai, Aravind; Nayak, Madhabika B; Greenfield, Thomas K; Bond, Jason C; Hasin, Deborah S; Patel, Vikram
Abstract : Background: Few population-based studies from low-income and middle-income countries have addressed adolescent drinking onset and its association with adult alcohol-related adverse outcomes. The aims of this study were to: (1) estimate the rate of adolescent drinking onset and its trend over time among men (2) describe demographic and socioeconomic factors associated with adolescent drinking onset; and (3) examine the association between adolescent drinking onset and adverse outcomes in later life, including hazardous or harmful alcohol use, heavy episodic drinking, alcohol dependence, injuries and psychological distress. Methods: Population-based survey of men (n=1899) from rural and urban communities in northern Goa, India. Analysis addressed age of drinking onset among those who reported ever drinking in their lifetime, and drinking patterns and consequences among current drinkers. Results: Adolescent drinking onset showed an increasing trend over time (p<0.001), from 19.5% for those born between 1956 and 1960 to 74.3% for those born between 1981 and 1985. Urban residence, Christian religion and low standard of living were associated with adolescent drinking onset. Adolescent drinking onset was associated with psychological distress (OR 2.82; 95% CI 1.41 to 5.63), alcohol dependence (OR 2.56; 95% CI 1.79 to 3.68), lifetime history of alcohol related injuries (OR 3.07; 95% CI 1.16 to 8.14), alcohol related injuries during the past year (OR 3.04; 95% CI 1.35 to 6.81), and a Alcohol Use Disorder Identification Test score ≥8 indicating hazardous or harmful alcohol use (OR 1.9; 95% CI 1.17 to 3.08) in adulthood. Conclusions: This study among men in Goa, India suggests a substantial increase in adolescent drinking onset in more recent birth cohorts. Consistent with other countries, adolescent drinking onset increased the likelihood of lifetime alcohol dependence, hazardous or harmful alcohol use, alcohol related injuries and psychological distress. These findings highlight the need for policies and programmes to delay drinking onset in India.